ESBL/pAmpC-Producing Escherichia coli Causing Urinary Tract Infections in Non-Related Companion Animals and Humans - Adriana Belas; Cátia Marques; Juliana Menezes; Luís Telo da Gama; Patrícia Cavaco-Silva; Constança Pomba (MDPI AG, 2022)
Urinary tract infections (UTI) caused by Escherichia coli are frequently diagnosed in humans and companion animals. Extended-spectrum beta-lactamase (ESBL)- and cephalosporinase (pAmpC)-producing Escherichia coli are worldwide-disseminated and frequently multidrug-resistant, hence leading to treatment failure and public health concerns. This study aimed to characterize and compare ESBL/pAmpC-producing E. coli strains causing community-acquired UTI in companion animals and non-related humans. Third-generation cephalosporin (3GC)-resistant E. coli (companion animals n = 35; humans n = 85) isolated from patients with UTI were tested against 14 antimicrobials following CLSI guidelines. PCR-based assays were used to detect the major E. coli phylogenetic groups, pathogenicity associated-islands (PAIs), virulence genes, and ESBLs/pAmpC resistance genes. ESBL/pAmpC-producing E. coli isolates were typed by multi-locus sequence typing (MLST) and PCR. E. coli strains from companion animals and humans shared two MDR high-risk clonal lineages: ST131 and ST648. To the best of our knowledge, this study reports the first description of E. coli ST131 clade C1-M27 and the clonal lineage ST131 clade A in humans with community-acquired UTI in Portugal. Considering that companion animals with UTI are generally treated at home by the owners, measures should be implemented to avoid the spread of multidrug-resistant high-risk clones to humans and their household environment.